Guardian of genome on the tract: Wild type p53-mdm2 complex inhibition in healing the breast cancer - S.K., Janani; S.P., Dhanabal; R., Sureshkumar; Sai Surya, Nikitha Upadhyayula; Chenmala, Karthika (Gene, 2021)
•Breast cancer has ruined women’s life. Since, it involves complex pathways.•P53 “Guardian of genome” plays a magnificent role in inhibiting cancer growth.•Key roles of p53: apoptosis, anti-angiogenesis, anti-metastatic, cell cycle arrest.•Directly/indirectly genes and proteins are targeted by p53 in anti-cancer activity.•P53 focuses on multiple pathways instead of one particular mechanism. Breast cancer acts as an assassin among women. According to WHO (world health organisation), about 6, 27,000 deaths have occurred in 2018 due to breast cancer. Since, the evolution of cancer involves many complicated pathway, in this article we have decided to focus on wild type p53. P53 is also called as tumor suppressor gene. As the name suggest, p53 is a real guardian of genome, if it is not mutated or subjected to degradation. It can perform a wide range of activities during cancer progression. It either stimulates or inhibits the genes or proteins that are responsible for cell cycle arrest, apoptosis, anti-angiogenic activity and anti-metastatic activity. At times, the p53 will be unable to produce its action due to various reasons like mutation or degradation by other proteins or degrading ligases. Since, we are focusing on wild type p53, it will be inhibited occasionally by mdm2 resulting in proteosomal degradation of p53. However, this condition can be prevented by possible treatment regimen. With the above points in mind, we have focused on p53 activation, complex formation between p53 and mdm2, and inhibition of the complex in order to free p53 and allow them to perform their action for rehabilitation of cancer. Furthermore, we have also discussed pathways involved in eradicating cancer through p53 activation. By considering the following aspects, hope that p53 can be considered for management of breast cancer.